Active Site-inactivated Factors VIIa, Xa, and IXa Inhibit Individual Steps in a Cell-based Model of Tissue Factor-initiated Coagulation - Kjalke, Marianne; Monroe, Dougald M.; Hoffman, Maureane; Oliver, Julie A.; Ezban, Mirella; Roberts, Harold R. (Thrombosis and Haemostasis, 1998)
Factors VIIa, Xa, and IXa play different roles in the initiation of tissue factor-dependent coagulation. The consequences of competing with the different enzymes were investigated, thereby examining the effects of inhibiting the initiation process at different steps. Active site-inactivated factors VIIa, Xa, and IXa (FVIIai, FXai, and FIXai, respectively) were added to various cell-based assays mimicking the individual steps in tissue factor-initiated coagulation. In an assay involving tissue factor-expressing monocytes, coagulation proteins and unactivated platelets, FVIIai and FXai inhibited platelet activation and thrombin generation while FIXai only inhibited thrombin generation. FVIIai inhibited factor Xa generation and subsequent thrombin generation on monocytes, while FXai inhibited thrombin generation on the monocytes as well as on the activated platelets. FIXai had no effect on factor Xa or thrombin generation on the monocytes, but inhibited factor Xa and subsequent thrombin generation on the activated platelets. FVIIai had no effect on the reactions taking place on the activated platelets. The data confirm a model where tissue factor/factor VIIa mediates factor Xa generation and subsequent prothrombin activation on the tissue factor-bearing cells. Thrombin then activates platelets, which serve as the physiologically important surface for large-scale thrombin generation.